Ethnic identity and economic welfare - Bagce, Sinem; Yilmaz, Ensar; Kilic, Ibrahim Engin (ELSEVIER, 2021)
In this study, we use rich survey data to understand the determinants of labor market success across refugees of different ethnicities in Turkey. In particular, we examine individual personality traits and integration barriers by considering metrics of refugees' proximity to Turkey based on their home countries' levels of cultural distance. Using microdata, we derive a refined index called ethnosizer scale to grasp the distance of minor ethnic identities in Istanbul to the dominant identity. Utilizing this parameter, we aim to analyze how the degree of commitment to the local society's culture affects the economic welfare of refugees in Istanbul, in terms of their earnings, participation in labor markets and wage gap compared to the natives.
Keywords: Ethnosize; Ethnic identity; Refugees; Wage gap; WAGE; EARNINGS; DISCRIMINATION; ASSIMILATION; MIGRATION; QUALITY; GERMANY; GAP; Business & Economics